CRIMINAL LAW PROTECTIONl AGAINST DEPRIVATION OF ANIMAL RIGHTS IN INDONESIAN ZOO'S - Dahlia (Pusat Unggulan Ipteks-PUI Universitas Jambi, 2025)
The state is responsible for protecting animals under conservation organizations. Wildlife can also be utilized to fulfill other needs, such as education and recreation. One place for recreation is a zoo. The establishment and maintenance of animals must follow established procedures and regulations. Zoos in Indonesia were created with the aim of conserving wildlife outside their natural habitat so that they do not become extinct. Apart from being a place of conservation, zoos also serve as a means of recreation, education and research. Therefore, zoos have full responsibility for the survival of the animals they protect, including their nutritional needs and psychological health. Unfortunately, facilities in zoos are deteriorating and the animals in them are not well cared for. Many carnivorous animals are sick and underweight, and many animals die due to the lack of repairs and the lack of legal protection given to animals in zoos.